'The most notorious trouble spot along the entire border': exploring the dynamics of political violence in an Irish border town, 1971–1974. Issue 4 (1st October 2020) - Mulroe, Patrick
ABSTRACT: Levels of violence on the Irish border escalated significantly during the years 1971–1974. Frequently, the British government alleged that the IRA was using the territory of the Republic of Ireland as a base from which to launch attacks. This paper will examine the southern border town of Lifford, which featured prominently in British complaints. Despite the significance of border violence, there has been a tendency for research on the Northern Ireland Troubles to focus on the urban centres. Evidence presented shows that the IRA was extremely active in the Lifford area. The Irish security forces were ill-equipped to deal with the threat and there are allegations that low-level collusion occurred. The Irish government was under diplomatic pressure to act with regard to the situation for some time. The IRA eventually over-escalated its campaign, engaging in military activity south of the border, prompting a significant security response from the Irish state and a subsequent decline in violence. It is concluded that failings by the Irish security forces were due to a range of factors including sympathy for northern nationalists, lack of resources, organisational weakness, and a fear of acting in case violence spread to the Republic of Ireland.